Experimental animal models of acute respiratory distress syndrome: one-hit and two-hit establishment application - Zhao, Yue; Li, Xin; Ou, Yanhua; Cai, Xiangran; Huang, Weijian; He, Shuhua; Liang, Sisi; Wang, Ning; Song, Linliang; Fang, Meixia; Niu, Hatitao; He, Jun (Frontiers in Immunology, 2025)
BackgroundAcute respiratory distress syndrome (ARDS) is a complex syndrome with multiple risk factors that can lead to acute respiratory failure and, in turn, high morbidity and mortality. To clarify the syndrome’s underlying pathomechanisms and develop novel therapies, we have summarized and analyzed a series of chief cause-induced animal models of ARDS.AimAlthough various animal models have been developed to represent the traits of human ARDS based on clinical symptoms and the yardstick of positive clinical trials, each model has unique features that reflect only part of the characteristics modeled. In response, this review aims to investigate characteristics of ARDS in current animal models and offers new strategies and insights for developing animal models aimed at capturing the features of human ARDS.ConclusionThis review summarizes the physiological characteristics of animals used in models of ARDS and evaluates the advantages and disadvantages of the chief cause-induced models for modeling human ARDS in animals, for results that can inform the establishment, assessment, and experimental study of ARDS in animal models.